Mediating effect of safety knowledge on the relationship between safety competency and safety attitude among oil and gas on-shore contractor workers in Bintulu, Sarawak - Saini, Sazali; Adam Assim, Mohd Ibrani Shahrimin; Marzuki, Omar Faruqi; Yaccob, Yasmin binti (Human Resource Management Academic Research Society (HRMARS), 2023)
Construction site accidents have been found to be mainly caused by workers unsafe behaviors, largely due to nonchalant attitude towards safety hazards. Workers often tend to underestimate safety risks on construction site, which limits their ability to identify hazardous situations. A growing number of studies indicate frameworks of research on safety knowledge articulate the skills, knowledge, and abilities for a skilled worker in the modern world. However, there exist a scarcity of the factors of workplace safety and health from most of the current study frameworks to prepare for the future workforce. Currently, an onshore oil and gas activity in Bintulu, which is in Sarawak warrant a deeper study on the contractor worker’s Safety Competencies to better understand of other factors that may influence it. Worker’s competency working in this industry needs to be strengthened as part of the element in Health, Safety and Environment Management System (HSEMS) requirement to ensure sustainable and safe operation of the plant as it contributes to HSE performance of the organization. The objectives of this study involve assessing contractor’s Safety competency and Safety attitude working in the oil and gas industry in Sarawak and analyzing the mediator effect of Safety Knowledge. A survey has been conducted to assess 450 contractor worker’s HSE competency. A self-administered with Likert scale questionnaire was used to collect the data. The survey results shows that education level, experience and competency played key important roles in ensuring safe execution of the work and support the hypothesis that knowledge do influence the competency as mediating factor. Based on the findings, further studies will provide the organization a better understanding of safety knowledge and to strategize their Induction Program in ensuring that their future workforce are competent technically as well as their safety attitude prior entering the industry.